Language status in children with normal language development and children suffering from specific language impairment - Mildner, Vesna; Vidović, Ana (2008)
Specific language impairment (SLI) is a developmental language impairment of unidentified (presumed hereditary) etiology. The general development of children suffering from SLI is neat and harmonious: they have no hearing problems ; their motor, emotional, social and cognitive development is in accordance with their age. Children suffering from SLI present with no neurological impairment, but this does not mean that the cause of their difficulties is not in the central nervous system. Their language development is delayed but it is also different than in their peers. The aim of this study was to analyze the speech of Croatian children suffering from SLI, and compare it with the speech of children with normal language development (NLD). The analysis was based on their ability to repeat 14 sentences differing in length and level of complexity, and the ability of narration (retelling), based on the mean length of utterance and the number of verbs used in the narrated text. Two girls and three boys suffering from SLI and two girls and three boys with NLD were studied. All subjects were five years old. The SLI children were less successful in repeating the sentences than the control group, especially when repeating grammatically more complex sentences. The SLI children were also less successful in retelling the story, which was manifested as considerably shorter length of utterance and a smaller number of verbs used in the narrative text.
Projekt MZOS
Projekt MZOS
ENG